Propranolol treatment for infantile hemangioma does not increase risk of childhood wheezing. Issue 8 (7th March 2017) - Mei‐Zahav, Meir; Blau, Hannah; Hoshen, Moshe; Zvulunov, Alex; Mussaffi, Huda; Prais, Dario; Stafler, Patrick; Steuer, Guy; Lapidoth, Moshe; Amitai, Dan Ben
Abstract: Objective: Propranolol is the treatment of choice for infantile hemangiomas requiring medical intervention. Although contraindicated in asthma, its bronchoconstrictive effect in infants and children has not been extensively studied. We aimed to assess the incidence of wheezing episodes in infants and children treated with propranolol for infantile hemangiomas. Study Design: A retrospective case‐control study. Setting: a tertiary pediatric hospital. Patients: All Children followed for infantile hemangioma between 2009 and 2014. Children followed conservatively served as control group and were matched 1:1 for gender and month of birth by random matching to children treated with propranolol. Interventions: All respiratory episodes (asthma, wheezing, stridor, and pneumonia) and respiratory associated hospitalizations were recorded from hospital records, from the primary care physician visits records and pharmacy prescriptions. The main outcome measure was the incidence of respiratory episodes in the treatment and the control groups. Results: A total of 1828 clinic visits were reviewed for 683 children. In addition, primary care physician visits records were available in 80% of them. Two hundred and sixteen children were treated with propranolol. Incidence of respiratory episodes and recurrent respiratory episodes was similar in the propranolol and control groups (8.3% vs 12%, P = 0.265; 3.7% vs 6.5%, P = 0.274, respectively). Time to first episode was similar in the treatment and control groups (5.03 ± 3.32 vs 4.45 ± 3.21 months, respectively, P = 0.09). Respiratory hospital admission rate was similar in both groups. Conclusions: Propranolol treatment does not exacerbate wheezing episodes in infants and children.